TEACHING MEDIA THROUGH MEDIA IN THE ENGLISH CLASSROOM - Yunusova, Zilola (Educational Research in Universal Sciences, 2022)
The media in the English Language development establishes a link between the human resources and the non-human resources. They are the different kinds of things which the teachers and the students use in the teaching learning process. This study will report on an attempt to integrate media literacy education into the language classroom—a Media English course offered in an English department. The paper will start with a review of the literature on media literacy education. It will then describe the course and the classroom activities adopted.